2021
DOI: 10.1002/ajcp.12544
|View full text |Cite
|
Sign up to set email alerts
|

Community Greening, Fear of Crime, and Mental Health Outcomes

Abstract: Unmaintained vacant land in urban areas is associated with a number of negative outcomes for residents of urban areas, including mental and physical health, safety, and quality of life. Community programs which promote land parcel maintenance in urban neighborhoods have been found to reverse some of the effects that unmaintained land has on nearby residents. We explored how land parcel maintenance is associated with mental health outcomes using data collected in Flint, MI in 2017–2018. Trained observers assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…Efforts to eliminate and demolish abandoned homes have reduced firearm violence by 11% in Detroit, Michigan and other community greening projects have reduced gun assaults and overall community violence 37. Improving the maintenance of vacant lots through community greening projects also reduces residents fear of crime and improves overall community mental health outcomes 38…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to eliminate and demolish abandoned homes have reduced firearm violence by 11% in Detroit, Michigan and other community greening projects have reduced gun assaults and overall community violence 37. Improving the maintenance of vacant lots through community greening projects also reduces residents fear of crime and improves overall community mental health outcomes 38…”
Section: Discussionmentioning
confidence: 99%
“…Neighborhood physical disorder is an indicator of disinvestment that might impact health behaviors through psychosocial stress pathways ( Burt et al, 2022 , Keyes et al, 2012 , Mayne et al, 2018 , O'Brien et al, 2019 ). Such explanations posit that residents of higher physical disorder areas perceive this higher disorder ( O'Brien et al, 2019 ), which triggers neuroendocrine pathways involved in maladaptive stress responses potentially leading to engagement in unhealthy behaviors ( Agorastos and Chrousos, 2022 , McEwen, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…Observed neighborhood physical disorder – visual indicators of disinvestment acting as neighborhood stressors – is one such factor ( Branas et al, 2018 , Raleigh and Galster, 2015 , Sampson and Raudenbush, 2004 ). Neighborhood physical disorder has been gaining attention in the sociologic ( Burt et al, 2022 , O'Brien et al, 2022 ), epidemiologic ( Keyes et al, 2012 , Mayne et al, 2018 , Messer et al, 2012 , Meyers et al, 2013 , Plascak et al, 2022 ), and urban revitalization ( Branas et al, 2018 ) literatures as findings have suggested it may affect health through psychosocial and behavioral pathways. Several studies have reported associations between higher observed neighborhood physical disorder and greater tobacco smoking and alcohol consumption ( Brown et al, 2014 , Furr-Holden et al, 2011 , Keyes et al, 2012 , Mayne et al, 2018 , Messer et al, 2012 , Meyers et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Individual benefits can include access to fresh food, increased physical activity, social development, income benefits, and environmental education (Guitart et al., 2012; Litt et al., 2011). Community benefits include increased real estate values, reduced crime, enhanced greenspace, and environmental equity (Burt et al., 2021; Egli et al., 2016; Knobel et al., 2021; Kondo et al., 2020; Lawson, 2005; Voicu and Been, 2008).…”
Section: Introductionmentioning
confidence: 99%